Adaptation of velogenic Newcastle disease virus in Vero cells: velogenicity of virus unaltered after adaptation - RAVINDRA, P. V.; RATTA, B.; CHATURVEDI, U.; PALIA, S. K.; SUBUDHI, P. K; TIWARI, A. K. (Journal of the Hellenic Veterinary Medical Society, 2017)
In the present experiment, velogenic Newcastle disease virus (NDV) was adapted to Vero cells without the addition of exogenous trypsin. The cytopathic effect (CPE) in NDV-infected Vero cells was observed from passage 3 (P 3) onwards with concomitant increase in the haemagglutination (HA) and virus titres. The CPE was characterized by rounding of cells, their detachment from the surface and syncytia formation. The Vero-adapted NDV was confirmed by reverse transcription-polymerase chain reaction (RT-PCR), which detected the amplification of haemagglutinin neuraminidase (HN) gene from virus-infected cells. The mean death time (MDT) of 58 hours upon inoculation to embryonated chicken eggs and the intravenous pathogenicity index (IVPI) of 2.12 following inoculation to SPF chicken suggested that Vero adapted virus retained the velogenicity even after ten passages. Furthermore, the nervous signs and haemorrhages in the pro-ventriculus of birds that died at day 5 post inoculation with PIO virus confirmed that the Vero-adapted NDV was a neurotropic viscerotropic velogenic strain.